Penerapan Model PBL Terintegrasi Flipped Classroom Terhadap Kemampuan Pemecahan Masalah Pada Materi Sistem Pertahanan Tubuh - Marviany, Anggi; Wicaksana, Ervan Johan; Astriawati, Fitri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to investigate the effectiveness of the integrated Problem-Based Learning (PBL) model with the Flipped Classroom approach on studentsâ€™ problem-solving skills in biology learning for Grade XI Phase F at SMAN 1 Kota Jambi. The main issue addressed in this research is the suboptimal implementation of the PBL model in the classroom due to limited instructional time. This study employed a quasi-experimental design using the nonequivalent pretest-posttest control group design. The research was conducted at SMAN 1 Kota Jambi during the even semester of the 2024/2025 academic year. The population consisted of Grade XI Phase F students, with Class XI F2 assigned as the experimental group and Class XI F7 as the control group, selected through purposive sampling and random sampling techniques. Data were collected using observation sheets and essay test instruments. The research data were analyzed using a One-Way ANCOVA test. The results indicated a significant difference between the experimental and control groups based on the One-Way ANCOVA test results [F(1,69) = 53.941, p < 0.001, Î·pÂ² = 0.439]. The obtained Partial Eta Squared value of 0.439 demonstrates a significant difference between the integrated Problem-Based Learning with Flipped Classroom model and the conventional Problem-Based Learning model. Based on these findings, it can be concluded that the integration of the Problem-Based Learning model with the Flipped Classroom approach is effective in enhancing the problem-solving skills of Grade XI Phase F students at SMAN 1 Kota Jambi.